First record of Cyrtogenius Strohmeyer in Europe, with a key to the European genera of the tribe Dryocoetini (Coleoptera: Curculionidae, Scolytinae) - Faccoli, Massimo; Simonato, Mauro; Toffolo, Edoardo Petrucco (Zootaxa, 2012)
The genus Cyrtogenius Strohmeyer, represented by the species C. luteus (Blandford, 1894), is reported for the first time in Europe. Many adults were collected for four consecutive years (2009–2012) in various localities of northern Italy in both multifunnel and cross-vane traps baited with multilure blends. A diagnosis of the species and a revised key to the European genera of tribe Dryocoetini Lindemann is also reported. An explanation is suggested for the increasing number of recent introductions of exotic scolytids into Europe.